Behavioral Patterns of Economic Decision-Making at the Local Level: The Theoretical Principles - Patytska Khrystyna O. (Bìznes Inform, 2021)
The article is aimed at defining the behavioral patterns of economic decision-making at the level of territorial hromadas. The main difference between traditional economic science and behavioral economics is substantiated. The traditional economic model is formed around the behavior of the «economic man», which is characterized by rationality in decision-making, completeness of self-control, limitless cognitive skills, restricted self-interest and stability of preferences; behavioral economics – around the behavior of Humans, which is characterized by numerous behavioral biases, changing preferences, acquiring new skills and further learning, social impact, altruism, etc. Two levels of behavioral economics are highlighted: micro- and macro-levels. The first level involves the study of the peculiarities of individual decision-making, the second involves the study of the impact of the behavior of economic agents on the development of the financial market together with economic growth of territories. It is substantiated that the study of behavioral patterns at the local level in the State requires, first of all, an analysis of the peculiarities of individual decision-making in the context of the developments in the micro-behavioral economics. The principles of behavioral economics, which have a significant impact on the behavioral characteristics of economic entities in the process of economic decision-making, are systematized. Cognitive biases and heuristic methods, features of choice architecture that influence decision-making are defined. Prospects for further research in this direction are the introduction of the principles of behavioral economics in the context of the development of territorial hromadas, in particular, taking into account tendencies in decentralization and the increasing impact of the behavior of certain subjects or groups of such entities on the development of the territory with a decrease in the size of the administrative-territorial unit.